(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Acute odontogenic periostitis is a purulent type of the disease that causes infection of the periosteum of the alveolar process and localized inflammation in periodontal tissues. Purulent periostitis typically affects the lower jaw. Keywords: odontogenic periostitis, odontogenic inflammation, periodontitis.